(untitled) (The Peerian Journal, 2025)
The definite integral is one of the important concepts in mathematics and is widely used in many fields, including economics. Applications of the definite integral in economic problems are important in the analysis of many processes, such as production, consumption, costs and income. This article provides information on how the definite integral is applied to economic problems